NON-PERIODIC BIFURCATIONS FOR SURFACE DIFFEOMORPHISMS - Horita, Vanderlei [UNESP]; Muniz, Nivaldo; Sabini, Paulo Rogerio (Amer Mathematical Soc, 2015)
We prove that a positive probability subset of the boundary of the set of hyperbolic (Axiom A) surface diffeomorphisms with no cycles H is constituted by Kupka-Smale diffeomorphisms: all periodic points are hyperbolic and their invariant manifolds intersect transversally. Lack of hyperbolicity arises from the presence of a tangency between a stable manifold and an unstable manifold, one of which is not associated to a periodic point. All these diffeomorphisms that we construct lie on the boundary of the same connected component of H.